Sexual function and depressive symptoms in primary infertile women with vitamin D deficiency undergoing IVF treatment - Zeynep Ozturk Inal; Hasan Ali Inal; Umit Gorkem (Elsevier, 2020)
Objective: To investigate the prevalence of female sexual dysfunction (FSD) and depression in primary infertile women with 25-Hydroxyvitamin D3 (25-OH VD) deficiency undergoing in-vitro fertilization (IVF)-intracytoplasmic sperm injection (ICSI) treatment. Materials and methods: A total of 80 women with 25-OH VD3 deficiency (<20 ng/mL = group 1), 80 women with 25-OH VD3 insufficiency (20-29.9 ng/mL = group 2), and 80 women with a normal 25-OH VD3 level (30-60 ng/mL = group 3) were included the study. Female sexual function and depression were measured using the Female Sexual Function Index (FSFI) and Beck Depression Inventory (BDI). Results: No statistically significant differences were found among the groups in terms of demographic characteristics, baseline and laboratory parameters. Statistically significant differences were observed among the groups with regard to FSD and depression. The FSFI (group 1 = 22.46 ± 2.13, group 2 = 25.82 ± 2.13 and group 3 = 28.66 ± 2.13, respectively) and sexual domain scores were low in women with 25-OH VD deficiency, and the number of women with depression (BDI score ≥ 17) was high (p < 0.05). Correlation analysis showed that the sexual domain scores were positively correlated with the 25-OH VD level, and the BDI score showed a significant negative correlation with the total FSFI score and 25-OH VD levels. Conclusion: The 25-OH VD status was associated with FSD and depression and that the degree of sexual dysfunction could depend on the severity of 25-OH VD levels. Further studies are needed to elucidate this issue. Keywords: Depression, In-vitro fertilization, Sexual function, 25-Hydroxyvitamin D3